Comparison between the vitek immunodiagnostic assay system and PCR for the detection of Salmonella spp. in foods (2013)
Objectives: To compare the methods of the automated Immunodiagnostic Assay System and the Polymerase Chain Reaction (PCR) to detect Salmonella spp. In food sold in the city of Santa Marta -Colombia. Materials and methods: The standardization of the PCR for detecting Salmonella spp was previously reported by us within 12 hours. The determinations were carried out with the help of the Public Health Laboratory of Magdalena, Colombia. 65 samples of food were studied: beef 14(21.5%), sausages 18(27.7%), chicken 7(10.8%), fish 3(4.6%), flours 13(20%), dairy products 5(7.7%) sauces 4(6.2%) y salads 1(1.5%) in the city of Santa Marta-Colombia between September and November 2010. A microbiological analysis was done on the 65 samples to determine Salmonella spp. in the Public Health Laboratory of Magdalena according to protocol of automated Vitek Immunodiagnostic Assay System. An aliquot of no selective pre-enrichment was sent to the molecular biology laboratory of Cooperativa de Colombia University to be analyzed for PCR. Results: The results show that the food analyzed in the public health laboratory presented Salmonella spp. only in sausages 5/65 (7.7%), while these samples analyzed using PCR showed Salmonella spp. in 36/65 (55.4%). Conclusions: The results indicate that PCR can be applied to get faster and better results to do regular epidemiological studies.